Inhibition of Bovine Enterovirus Infection by Magnolol via Modulating the Gut Microbiota in Mice - Junying Hu; Qun Zhang; Dan Liu; Xuyuan Cui; Qianying Wang; Wenjie Gong; Xinping Wang (Viruses)
Bovine enterovirus (BEV) infection is one of the important infectious diseases that cause digestive and respiratory symptoms in cattle, posing a significant threat to the cattle industry. Currently, no vaccines or therapeutic drugs are available for this disease. In our study, we utilized a mouse model to investigate the effects of BEV infection on the gut microbiota and examine the therapeutic potential of magnolol (Mag), a polyphenolic bioactive substance, in terms of BEV infection. BEV infection significantly altered the microbiota composition, where the abundance of some beneficial bacteria, such as Lactobacillaceae and Lactobacillus, was markedly reduced. Mag effectively inhibited BEV infection in vivo. Upon BEV infection, Mag treatment reduced the α-diversity of the microbiota, with statistically significant differences on day 3 post-infection compared to the Mag-untreated group. More interestingly, Mag treatment significantly reversed the effect of BEV infection on the Lactobacillaceae and Lactobacillus abundance, indicating that Mag positively regulates beneficial bacteria. The fecal microbiota transplantation (FMT) experiment demonstrated that feces from Mag-treated mice significantly decreased the virus loads in the small intestine samples of BEV-infected mice. These findings demonstrate the interaction between BEV infection and the gut microbiota and highlight the important regulatory role of the gut microbiota in Mag’s anti-BEV effects, opening up a new avenue for preventing and controlling BEV infection via targeted modulation of the gut microbiota.